2007
DOI: 10.1634/stemcells.2006-0828
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Bone Marrow-Derived Stem Cells to Endometrium and Endometriosis

Abstract: Bone marrow-derived cells (BMDCs) can differentiate into nonhematopoietic cells, suggesting that BMDCs may contribute to the maintenance of multiple tissues. Donorderived bone marrow cells have been identified in human uterine endometrium. Here, two murine models were used to investigate the contribution of nonendometrial stem cells to endometrium. We investigate whether BMDCs can localize to uterine endometrium and to endometriosis. After bone marrow transplantation, male donor-derived bone marrow cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
336
2
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(360 citation statements)
references
References 26 publications
12
336
2
10
Order By: Relevance
“…Our preliminary results indicate that the percentages of single cells positive for SALL4 and OCT4 we detected in the stroma of endometriotic tissues are comparable to those found by Gotte M et al for Musashi-1-positive cells (data not shown). The contribution of stem cells to endometriosis has been hypothesized in many reports of studies and reviews (45,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary results indicate that the percentages of single cells positive for SALL4 and OCT4 we detected in the stroma of endometriotic tissues are comparable to those found by Gotte M et al for Musashi-1-positive cells (data not shown). The contribution of stem cells to endometriosis has been hypothesized in many reports of studies and reviews (45,14).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, also conducted in murine models, demonstrated that stem cells in endometrium derive from bone marrow (14).…”
Section: Expression Pattern Of Stemness-related Genes In Human Endomementioning
confidence: 95%
“…Another field of study is the potential role of multipotent endometrial stem cells in the pathophysiology of diseases such as endometriosis, endometrial hyperplasia, endometrial cancer, and adenomyosis, which are associated with abnormal endometrial proliferation (Gargett 2004, 2006, Du & Taylor 2007. Alterations in the number, function, regulation, and location of endometrial stem/progenitor cells may be involved in the pathology mechanisms of these endometrial diseases.…”
Section: Discussionmentioning
confidence: 99%
“…31 It is not clear, however, whether or not there are multiple classes/gradations of stem/progenitor cells that can give rise to the glandular epithelium and stromal cells. 31,42 In contrast to this concept there are those who have provided evidence to suggest the bone marrow cells can give rise to endometrial cells 30,43 inferring that the bone marrow may harbor a stem cell that has the potential to become an endometrial cell whether it be epithelial or stromal.…”
Section: Discussionmentioning
confidence: 99%